2017
DOI: 10.1007/s40843-016-9005-9
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-Fe3O4 nanocomposites as high-performance antifungal agents against Plasmopara viticola

Abstract: Plasmopara viticola, a causal agent of grapevine downy mildew, is a widely distributed pathogen, which can cause destructive disease in field-grown grapevines. Although fungicides are used to treat the disease, fungicide-resistant strains have been emerging. In this study, we developed graphene oxide (GO)-Fe3O4 nanocomposites, which could effectively repress the germination of sporangia and inhibit the development of downy mildew. 50 μg mL −1 GO-Fe3O4 showed excellent protective and fungicidal activities. 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…2.1. Synthesis of Cu/PDA/RGO nanosheets: GO was prepared according to the procedure described by Wang's team [27]. Then the Cu/PDA/RGO nanosheets were typically synthesised as follows: 200 mg GO was dispersed in 200 ml DI water, and the resulting suspension was sonicated in an ice-bath for 1.5 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1. Synthesis of Cu/PDA/RGO nanosheets: GO was prepared according to the procedure described by Wang's team [27]. Then the Cu/PDA/RGO nanosheets were typically synthesised as follows: 200 mg GO was dispersed in 200 ml DI water, and the resulting suspension was sonicated in an ice-bath for 1.5 h.…”
Section: Methodsmentioning
confidence: 99%
“…GO was prepared according to the procedure described by Wang's team [27]. Then the Cu/PDA/RGO nanosheets were typically synthesised as follows: 200 mg GO was dispersed in 200 ml DI water, and the resulting suspension was sonicated in an ice‐bath for 1.5 h. Then 200 mg dopamine hydrochloride and 200 ml Tris‐buffer solution (10 mM, pH 8.5) were added to the above suspension and subsequently stirred for 12 h at room temperature to obtain the composites of reduced GO (PDA/RGO).…”
Section: Methodsmentioning
confidence: 99%
“…The Fe 3 O 4 NPs and graphene oxide (GO) were prepared using the method previously described by our group [8, 9]. To prepare PGFA composites, dopamine hydrochloride (10 mg) and Fe 3 O 4 NPs (12 mg) were added to 10 ml of GO aqueous dispersion (2.5 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Downy mildew is a disease caused by Plasmopara viticola in grapes plants that leads to extremely heavy yield loss. To combat the disease, a nanocomposite construct consisting of Graphene oxide (GO) and Iron oxide (Fe 3 O 4 ) as GO-Fe 3 O 4 nanocomposite was developed [ 39 ]. The study demonstrated that the pretreatment of the leaf discs with nanocomposite followed by inoculation with P. viticola sporangium suspension strongly inhibited the spore germination.…”
Section: Nanocomposites and Their Mode Of Action On The Fungal Phymentioning
confidence: 99%
“…This effect may be attributed to the blockage of the water channels of sporangia by surface adsorption of the nanocomposites. From the images, it is evident that bare GO and Fe 3 O 4 possessed moderate spore germination inhibition activity while the nanocomposites triggered stupendous activity [ 39 ].…”
Section: Nanocomposites and Their Mode Of Action On The Fungal Phymentioning
confidence: 99%